Big air skateboarding - David, Jack, 1968- (Minneapolis, MN : Bellwether Media, 2008)
Action photographs and text provide an introduction to big air skateboarding, describing the sport, its equipment, and its history. Includes a glossary and resources.
Includes bibliographical references (p. 23) and index.
4.0
K-3
Keywords: Skateboarding -- Juvenile literature; Skateboarding; Skateboarding